COMMUNICATION PROBLEM, RISK AND LEADERSHIP ATTRIBUTES DURING TECHNOLOGY CHANGE INITIATIVE ON MULTINATIONAL ENERGY COMPANY - Ahmad Murtadho (European Scientific Journal, ESJ, 2013)
In Multinational enterprise, new global system project will affect a wide variety of business process. Changes made to the system are, in effect, changes made to the business processes themselves and these processes fall down in the face of the increased complexity of today's business and technology environments. Most of the companies rely on the digital system and technology to support their business activities. A competitive business environment make companies have to upgrade one company information technology system and process continuously. During the technology upgrade process, change in the management and organization behavior happen. This research discover the problems that happen during technology change initiative within its risk and the top management attribute that can mitigate the problem during the change.There are four main problems that discover during the research, which are lack of top management vision, failed to communicate vision and benefit of the change, negative attitude, and communication problem from internal project team. These problems lead to several potential risks for the project, which related to project budget, project schedule, project quality and project scope. Successful technology change within an organization on the change strategy addressing Leadership and top management attribute take critical role to contribute to successful outcomes in project implementation